Effect of Gamelan and progressive muscle relaxation on blood pressure in hypertensive patients - Ira Rahmawati; Firda Ayu Magfiroh; Budiono Budiono; Sulastyawati Sulastyawati (PAGEPress Publications, 2023)
Chronically elevated blood pressure was a prominent risk factor for cardiovascular diseases. The management of hypertension, especially in community settings, should combine pharmacological and non-pharmacological interventions. This study aimed to evaluate whether music-assisted progressive muscle relaxation (PMR) using Gamelan, Javanese classical music, could reduce blood pressure more effectively in hypertensive elderly individuals in Malang, Indonesia, than PMR alone. This study employed a pre-test and post-test study design with a control group. Fifty-eight respondents were randomly assigned to the intervention group (n = 31) and the control group (n = 27). Three respondents in the control group did not complete the study; thus, they were excluded from the analysis. The intervention group was trained and guided to perform PMR while listening to Gamelan. Meanwhile, the control group only received PMR. The intervention was conducted twice a week for 20 minutes for eight weeks. Dependent variables in this study were systolic and diastolic blood pressure, which were measured using an aneroid sphygmomanometer. Data were analyzed using descriptive statistics, paired t-tests, independent t-tests, and Mann-Whitney test. We found a significant decrease in systolic and diastolic blood pressure in both groups. A Mann-Whitney test showed that there was a significant difference in the reduction of systolic blood pressure in the intervention group compared to the control group (p = 0.000). Meanwhile, the independent t-test showed that the diastolic blood pressure in the intervention group reduced more significantly than that in the control group. The efficacy of Gamelan-assisted PMR in significantly reducing both systolic and diastolic blood pressure showcases the potential of such combined interventions in managing hypertension. We recommend Gamelan-assisted PMR as a complementary therapy for the elderly with primary hypertension.